Genomic analysis of the first KPC-producing Klebsiella pneumoniae isolated from a patient in Riyadh: A new public health concern in Saudi Arabia. Issue 4 (April 2020) - Alghoribi, Majed F.; Binkhamis, Khalifa; Alswaji, Abdulrahman A.; Alhijji, Ali; Alsharidi, Aynaa; Balkhy, Hanan H.; Doumith, Michel; Somily, Ali
Abstract: Klebsiella pneumoniae carbapenemase (KPC)-producing Enterobacteriaceae have been isolated from human patients in many countries across the globe but rarely in Saudi Arabia. Here we provide the genomic characterization of the first KPC-producing K. pneumoniae isolated from the urine of a patient in Riyadh, Saudi Arabia, who had a recent travel history to Egypt involving a medical procedure. Presence of KPC-encoding gene initially detected with the Xpert Carba-R assay was confirmed by traditional PCR. Susceptibility testing using the VITEK 2 system, E-test and microbroth dilution methods showed that the K. pneumoniae isolate, namely SA01_KPC-2, was resistant to all antibiotics except colistin and ceftazidime/avibactam. Whole-genome sequencing (WGS), performed on the Illumina Miseq instrument, identified the isolate as sequence type (ST) 383 and serotype KL30-D1 O1v2. Genome assembly of SA01_KPC-2 indicated the presence of two plasmids. Plasmid pSA01_KPC-2, of approximately 45.9 kb in size, harbored the bla KPC-2 flanked by IS Kpn27 and IS Kpn6 and had a backbone similar to published KPC-carrying IncX6 plasmids. The second plasmid pSA01_incHIB1, a derivative of published 372-kb plasmid pKpvST383, carried genes encoding virulence factors and resistance to five classes of antibiotics. The isolation of the first KPC producer in Saudi Arabia requires high attention and rapid interventions to prevent further spread.